IMPLEMENTATION OF GEOGEBRA IN MATHEMATICS TO IMPROVE THE SKILLS OF TEACHERS - Andri Rahadyan; Indra Kurniawan; Halimatussa'diah Halimatussa'diah (JMM (Jurnal Masyarakat Mandiri), 2023)
Abstract: GeoGebra is one of the programs designed to improve the effectiveness of mathematics learning. For this reason, mathematics teachers should be able to operate GeoGebra to deliver learning material that is more interesting for students. This service activity aims to improve the math teacher's skills in constructing geometric shapes and other mathematical objects in the GeoGebra application to make it easier for students to understand mathematical material that requires more realistic visualisation. The service's target is mathematics teachers at HSPG Bekasi, where as many as ten teachers participated in this training. The method used in this activity goes through 4 stages: assessment, planning and development, and implementation of online workshops. Teachers are introduced to GeoGebra software and how to use it according to mathematical material, namely building spaces and completing linear and quadratic equations. Evaluation is carried out by giving a project test. The results of community service are that teachers can visualise geometric shapes and mathematical objects in GeoGebra so that students will better understand the concept of the material provided. The results of the project tests that have been carried out obtained an average value of 85, so there is an increase in the skills of teachers who are very good at using GeoGebra.